Angiogenesis Inhibitors for the Treatment of Hepatocellular Carcinoma - Berretta, Massimiliano; Rinaldi, Luca; Di Benedetto, Fabrizio; Lleshi, Arben; De Re, Vallì; Facchini, Gaetano; De Paoli, Paolo; Di Francia, Raffaele (Frontiers in Pharmacology, 2016)
Background: Angiogenesis inhibitors have become an important therapeutic approach in the treatment of hepatocellular carcinoma (HCC) patients. The achievement of Sorafenib in prolonging overall survival of patients with HCC makes therapeutic inhibition of angiogenesis a fundamental element of the treatment of HCC. Considering the heterogeneous aspects of HCC and to enhance therapeutic efficacy, overcome drug resistance and reduce toxicity, the combination of antiangiogenic drugs with antiblastic chemotherapy (AC), radiotherapy or other targeted drugs have been evaluated. The issue is further complicated by the combination of antiangiogenesis with other AC or biologic drugs. To date, there is no planned approach to determine which patients are more responsive to a given type of antiangiogenic treatment. Conclusion: Large investments in the clinical research are essential to improve treatment response and minimize toxicities for patients with HCC. Future investigations will need to focus on utilizing patterns of genetic information to classify HCC into groups that display similar prognosis and treatment sensitivity, and combining targeted therapies with AC producing enhanced anti-tumor effect. In this review the current panel of available antiangiogenic therapies for the treatment of HCC have been analyzed. In addition current clinical trials are also reported herein.